Adrenal biopsy, as a diagnostic method, is associated with decreased overall survival in patients with T1/T2 adrenocortical carcinoma: A propensity score‐matched analysis. Issue 8 (23rd August 2021) - Naffouje, Samer A.; Sabesan, Arvind; Hallanger‐Johnson, Julie; Kirtane, Kedar; Gonzalez, Ricardo J.; Mullinax, John
Abstract: Introduction: The standard diagnosis for adrenocortical carcinoma (ACC) is clinical diagnosis (CD) based on radiographic and biochemical studies. Biopsy diagnosis (BD) is seldom required for the suspicion of secondary malignancy. We aim to study the impact of BD in the context of underlying T1/T2 ACC on overall survival (OS) compared with CD. Methods: National Cancer Database (NCDB) for endocrine malignancies was utilized. Only patients with non‐metastatic ACC, whose method of diagnosis and local disease extension were reported, and received a surgical adrenalectomy with curative intent were included. Patients were divided by disease stage into T1/T2, T3, and T4 groups. A propensity score match was applied to those with T1/T2 disease who received CD versus BD and the Kaplan–Meier method was used to compare OS. Results: In total, 4000 patients with ACC were reported in the database, 1410 met selection criteria. Eight hundred and thirty patients had T1/T2, 365 had T3, and 162 had T4 ACC. Of patients with T1/T2 ACC, 742 (89.4%) received CD versus 88 (11.6%) with BD. A propensity score was calculated per a multivariable regression model with 79 patients matched from each group. Exact matching was applied for margin status and adjuvant therapies. Kaplan–Meier analysis showed a significant difference in median OS between CD versus BD patients in the matched data set (103.89 ± 15.65 vs. 54.93 ± 8.22 months; p = 0.001). In all comers, patients with T1/T2 ACC and BD had comparable median OS to that of patients with T3 ACC (52.21 ± 9.69 vs. 36.01 ± 3.33 months; p = 0.446). Conclusion: BD in T1/T2 ACC could be associated with disease upstaging and worse OS outcomes.